Pengaruh Pendidikan TB Melalui Whatsapp Reminder Berkala Terhadap Tingkat Pengetahuan Remaja di SMA Negeri 2 Denpasar - I Dewa Putu Gede Putra Yasa; I Putu Bayu Suadnyana; N Adi Sumartawan; I Made Widastra (Jurnal Gema Keperawatan, 2020)
Tuberculosis that attacks adolescents aged 10-18 years tends to increase. Health education is one way to increase adolescent knowledge about how to prevent tuberculosis, one of the media that can be used for health education is WhatsApp. This study aims to determine the effect of TB education through WhatsApp periodic reminder on the level of knowledge of adolescents in SMA Negeri 2 Denpasar in 2019. The research design used was one-group pre-post test design. The number of samples was 44 people selected by quota sampling technique. The study was conducted in July to August 2019. Data collection used knowledge level questionnaires about TB. The results of this study the average value of knowledge of adolescents before being given health education at 11.68 and after being given health education at 19.02. Hypothesis testing uses paired t-test with p value = 0.001 (p 0.05). The conclusion of this research is the effect of TB education through WhatsApp periodic reminder on the level of knowledge of adolescents, then it is recommended to do health education using WhatsApp media